LGBTQ+ Intimacies in Southern Europe Citizenship, Care and Choice - Santos, Ana Cristina (Citizenship, Gender and Diversity, 2023)
This Open Access book argues that Southern European countries offer valuable, though historically overlooked, knowledge regarding intimate citizenship. Guided by the fundamental sociological question of how change takes place and, concomitantly, how law and social policy adjust to and/or shape the practices and expectations of individuals in the sphere of intimacy, this edited volume explores partnering, parenting and friendship issues from the perspective of lesbian, gay, bisexual, trans and queer people in Italy, Portugal and Spain. Chapters offer a cross-national understanding of the relationship between everyday practices of intimacy amongst LGBTQ people and national legal, political and policy contexts in terms of the recognition of otherwise 'intimate strangers'. The book contributes to further theoretical and policy debates about citizenship, care and choice, as well as, more broadly, sexuality, welfare, health and justice. This book will be of interest to scholars across Gender and Feminist Studies as well as Citizenship Studies, Law, Policy, and Politics.